Molybdenum nitride quantum dot / two-dimensional layered nitrogen carbide composite material and preparation and application thereof in lithium-sulfur battery diaphragm modification
By using the molybdenum nitride quantum dot/two-dimensional layered nitrogen carbide composite as the electrocatalyst for the lithium-sulfur battery separator, the problem of poor kinetics of polysulfide conversion reaction in lithium-sulfur batteries is solved, and the rapid transmission of lithium ions and high capacity is achieved improves electrochemical performance.
Patent Information
- Application Number
- CN202411232027.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2024-12-13
AI Technical Summary
Lithium sulfur batteries have low conductivity of sulfur and discharge product Li2S2/Li2S, poor kinetics of polysulfide conversion reaction, and the shuttle effect of soluble polysulfide during charging and discharge.
Molybdenum nitride quantum dot/two-dimensional layered nitrogen carbide composite material is used as the electrocatalyst for lithium-sulfur battery separator. Hydrothermal treatment and second-stage calcination are carried out by ultrasonic dispersing the molybdenum source and carbon source, and the MoNQDs/NC composite material is generated for use in the Modified the separator to achieve adsorption and catalyzing of polysulfides and accelerate lithium ion migration.
The electrochemical performance of lithium-sulfur batteries is improved, excellent rate performance and cycling performance are achieved, and the surface capacity is higher than that of commercial lithium-ion batteries under high sulfur loading.
Smart Images

Figure CN119118075A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium-sulfur battery materials, and specifically relates to a molybdenum nitride quantum dot / two-dimensional layered carbonitride composite material and its preparation and application in lithium-sulfur battery diaphragm modification. Background Art
[0002] Countries around the world are laying out low-carbon strategies, and the new energy storage industry is an important part of it. Among all energy storage systems, lithium-sulfur batteries have been sought after by researchers because of their high energy density, low pollution, and considerable economic efficiency. However, lithium-sulfur batteries also have their inevitable disadvantages. For example: low conductivity of sulfur and discharge products Li2S2 / Li2S, poor reaction kinetics of polysulfide conversion, and the shuttle effect of soluble polysulfides during charging and discharging. Among them, the shuttle effect is the most important factor affecting the performance of lithium-sulfur batteries.
[0003] In order to limit the shuttle effect, researchers have developed modification strategies from physical confinement to chemical adsorption to catalytic conversion. In the modification strategy of catalytic conversion, transition metal compounds, such as transition metal nitrides, oxides, phosphides and sulfides, have received widespread attention due to their excellent catalytic ability for polysulfide conversion. Among them, molybdenum nitride has an excellent intrinsic electronic structure and can achieve rapid electron exchange. However, in the prior art, molybdenum nitride prepared by programmed temperature nitridation is too large in size due to the spontaneous growth of crystals, the internal active sites cannot be exposed, and the bonding with the base conductive carbon material is weak, which limits the catalytic ability for polysulfides. Summary of the invention
[0004] In order to solve the problems existing in the prior art, the purpose of the present invention is to provide a molybdenum nitride quantum dot / two-dimensional layered carbonitride composite material and its preparation and application in the modification of lithium-sulfur battery diaphragms. The composite material has the ability to adsorb and catalyze polysulfides and accelerate the migration of lithium ions. Using it as an electrocatalyst for the modification of lithium-sulfur battery diaphragms can effectively improve the electrochemical performance of lithium-sulfur batteries.
[0005] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:
[0006] A method for preparing a molybdenum nitride quantum dot / two-dimensional layered carbonitride composite material comprises the following steps:
[0007] (1) ultrasonically dispersing a molybdenum source in deionized water to obtain a molybdenum source solution;
[0008] (2) ultrasonically dispersing the carbon source in the molybdenum source solution, performing solid-liquid separation after hydrothermal treatment, and drying to obtain a precursor powder;
[0009] (3) The precursor powder is mixed with a nitrogen source and calcined in two stages under an argon-hydrogen atmosphere to obtain a molybdenum nitride quantum dot / two-dimensional layered nitrogen carbonization composite material, denoted as MoNQDs / NC.
[0010] Preferably, in step (1), the molybdenum source is selected from one of ammonium molybdate, calcium molybdate and sodium molybdate. The molybdenum source selected in the present invention is easily soluble in water and can be evenly combined with the carbon source to generate highly dispersed and extremely small molybdenum trioxide in the subsequent hydrothermal reaction, laying a good foundation for the subsequent two-stage calcination nitridation to generate MoNQDs.
[0011] Preferably, in step (2), the carbon source is selected from one of urea, dicyandiamide and melamine, and the mass ratio of the carbon source to the molybdenum source is 1 to 10:1.
[0012] Preferably, in step (2), the temperature of the hydrothermal treatment is 180-240°C and the time is 12-24 hours. The present invention uses hydrothermal treatment to uniformly disperse quantum dot-sized molybdenum trioxide on the carbon source, and then generates MoNQDs and two-dimensional layered carbonized nitrogen synchronously through subsequent two-stage calcination and nitridation.
[0013] Preferably, in step (3), the nitrogen source is selected from one of polyacrylonitrile, ammonium chloride, hexamethylenetetramine and diaminomaleonitrile, and the mass ratio of the nitrogen source to the molybdenum source is 1 to 5:1.
[0014] Preferably, in step (3), in the argon-hydrogen atmosphere, the volume ratio of argon to hydrogen is 9-19:1; the specific process of the second-stage calcination is: first heating to 500-550°C, keeping warm for 1-3 hours, then heating to 750-850°C, keeping warm for 1-3 hours.
[0015] The present invention also provides a molybdenum nitride quantum dot / two-dimensional layered carbonitride composite material prepared by the above preparation method.
[0016] The present invention also provides an application of the above molybdenum nitride quantum dot / two-dimensional layered carbonitride composite material, which is used as a modified material to prepare a modified diaphragm for a lithium-sulfur battery.
[0017] Preferably, it is coated on a diaphragm base film to prepare the modified diaphragm.
[0018] The present invention also provides a modified diaphragm for a lithium-sulfur battery, comprising a base film and a modified material compounded on the surface of the base film, wherein the modified material comprises the molybdenum nitride quantum dot / two-dimensional layered carbonitride composite material.
[0019] In the present invention, the base film may be any well-known separator base film in the field of lithium-sulfur batteries. For example, the base film is at least one of PP and PE.
[0020] In the present invention, the modified material is prepared by mixing molybdenum nitride quantum dots / two-dimensional layered carbonitride composite material, conductive carbon black and polyvinylidene fluoride in a ratio of 8:1:1 in an N-methylpyrrolidone solvent.
[0021] The present invention also provides a lithium-sulfur battery, comprising a positive electrode, a diaphragm and a negative electrode which are compounded in sequence, wherein the diaphragm is the modified diaphragm described in the present invention.
[0022] The lithium-sulfur battery of the present invention, except for the modified diaphragm, may have conventional components and parts.
[0023] The present invention innovatively combines MoNQDs with two-dimensional layered NC in situ, where MoNQDs provide a large number of active sites for anchoring and catalyzing polysulfides. Its excellent intrinsic electronic activity can accelerate the conversion of polysulfides, and can also regulate the surface structure of NC to greatly increase the carrier migration rate. MoNQDs / NC is used as a diaphragm modification material to prepare a modified diaphragm for lithium-sulfur batteries, which can achieve excellent rate performance and cycle performance, and under high sulfur loading, it achieves a surface capacity higher than that of current commercial lithium-ion batteries.
[0024] The advantages of the present invention are as follows:
[0025] The MoNQDs / NC composite material of the present invention realizes the preparation of MoN of quantum dot size, and is in-situ combined with two-dimensional layered NC, which is used as a modified material to prepare a modified diaphragm for a lithium-sulfur battery. The lithium-sulfur battery using the diaphragm can achieve long-term and stable adsorption and catalysis of polysulfide conversion and rapid lithium ion transmission during the charge and discharge process, has excellent rate performance and cycle performance, and achieves a surface capacity higher than that of current commercial lithium-ion batteries under high sulfur loading conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a scanning electron microscope image of MoNQDs / NC prepared in Example 1.
[0027] Figure 2 This is a transmission electron microscope image of MoNQDs / NC prepared in Example 1.
[0028] Figure 3 This is a high-magnification transmission electron microscopy image of MoNQDs / NC prepared in Example 1.
[0029] Figure 4 The Tafel curves of the symmetrical cell of MoNQDs / NC prepared in Example 1 and NC prepared in Comparative Example 1.
[0030] Figure 5This is a rate performance diagram of MoNQDs / NC prepared in Example 1 and NC prepared in Comparative Example 1 as diaphragm modified materials in lithium-sulfur batteries.
[0031] Figure 6 This is a self-discharge performance diagram of MoNQDs / NC prepared in Example 1 and NC prepared in Comparative Example 1 as diaphragm modified materials in lithium-sulfur batteries.
[0032] Figure 7 The MoNQDs / NC prepared in Example 1 was used as a membrane modification material at a sulfur loading of 9.1 mg cm -2 Cycling performance diagram of lithium-sulfur battery. DETAILED DESCRIPTION
[0033] The following examples are intended to further illustrate the present invention so that those skilled in the art can better understand the present invention. However, the present invention is not limited to the following examples.
[0034] Example 1
[0035] The preparation method of the MoNQDs / NC composite material of this embodiment includes the following steps:
[0036] (1) Add 0.5 g of ammonium molybdate to 50 ml of deionized water and disperse it evenly by ultrasonic treatment;
[0037] (2) adding 4 g of melamine to the solution in step (1), dispersing it uniformly by ultrasonic treatment, and then performing hydrothermal treatment at 200° C. for 12 h. After the treatment, the product is filtered and then dried to obtain a precursor powder;
[0038] (3) The precursor powder obtained in step (2) was fully mixed with 1 g of hexamethylenetetramine, and then placed in a tube furnace under an argon-hydrogen atmosphere at 10 °C min -1 The temperature was raised to 520℃ at a rate of 2℃min, kept at this temperature for 2h, and then -1 The temperature was raised to 800 °C at a rate of 1.5 °C and kept at that temperature for 2 h. After cooling, the target material MoNQDs / NC was obtained.
[0039] like Figure 1 Shown is the scanning electron microscope image of MoNQDs / NC, where separated two-dimensional flake morphology can be observed.
[0040] like Figure 2 Shown is the transmission electron microscopy image of MoNQDs / NC, where the uniform distribution of nanoparticles can be seen.
[0041] like Figure 3 As shown, this is a high-magnification transmission electron microscopy image of MoNQDs / NC. It can be seen that the nanoparticles are MoN quantum dots with a size of only about 5nm.
[0042] Example 2
[0043] The preparation method of the MoNQDs / NC composite material of this embodiment includes the following steps:
[0044] (1) Add 0.5 g of sodium molybdate to 50 ml of deionized water and disperse it evenly by ultrasonic treatment;
[0045] (2) 5 g of urea was added to the solution in step (1), and the mixture was dispersed uniformly by ultrasonic treatment, and then hydrothermally treated at 200° C. for 12 h. After the treatment, the product was filtered and dried to obtain a precursor powder;
[0046] (3) The precursor powder obtained in step (2) was thoroughly mixed with 2 g of ammonium chloride, and then placed in a tube furnace under an argon-hydrogen atmosphere at 10 °C min -1 The temperature was raised to 520℃ at a rate of 2℃min, kept at this temperature for 2h, and then -1 The temperature was raised to 800 °C at a rate of 1.5 °C and kept at that temperature for 2 h. After cooling, the target material MoNQDs / NC was obtained.
[0047] After testing, the MoNQDs / NC prepared in Example 2 was used as a diaphragm modification material in a lithium-sulfur battery. At a current density of 2C, the initial discharge capacity was 885 mAh g -1 After 100 cycles of charge and discharge, the capacity attenuation rate is 0.08%, which has good cycle performance.
[0048] Example 3
[0049] The preparation method of the MoNQDs / NC composite material of this embodiment includes the following steps:
[0050] (1) Add 0.5 g of sodium molybdate to 50 ml of deionized water and disperse it evenly by ultrasonic treatment;
[0051] (2) adding 2 g of dicyandiamide to the solution in step (1), dispersing it uniformly by ultrasonic treatment, and then hydrothermally treating it at 190° C. for 24 h. After the treatment, the product was filtered and then dried to obtain a precursor powder;
[0052] (3) The precursor powder obtained in step (2) was fully mixed with 1 g of diaminomaleonitrile, and then placed in a tube furnace under an argon-hydrogen atmosphere at 5 °C min -1 The temperature was raised to 520℃ at a rate of 2℃min, kept at this temperature for 2h, and then -1 The temperature was raised to 800 °C at a rate of 1.5 °C and kept at that temperature for 3 h. After cooling, the target material MoNQDs / NC was obtained.
[0053] After testing, the MoNQDs / NC prepared in Example 3 was used as a diaphragm modification material in a lithium-sulfur battery. At a current density of 2C, the initial discharge capacity was 901 mAh g -1 After 100 cycles of charge and discharge, the capacity attenuation rate is 0.07%, which has good cycle performance.
[0054] Example 4
[0055] The preparation method of the MoNQDs / NC composite material of this embodiment includes the following steps:
[0056] (1) Add 1 g of ammonium molybdate to 50 ml of deionized water and disperse it evenly by ultrasonic treatment;
[0057] (2) adding 5 g of melamine to the solution in step (1), dispersing it uniformly by ultrasonic treatment, and then performing hydrothermal treatment at 220° C. for 12 h. After the treatment, the product is filtered and then dried to obtain a precursor powder;
[0058] (3) The precursor powder obtained in step (2) was fully mixed with 4 g of polyacrylonitrile, and then placed in a tube furnace under an argon-hydrogen atmosphere at 2 °C min -1 The temperature was raised to 520℃ at a rate of 1℃min -1 The temperature was raised to 800 °C at a rate of 1.5 °C and kept at that temperature for 2 h. After cooling, the target material MoNQDs / NC was obtained.
[0059] After testing, the MoNQDs / NC prepared in Example 4 was used as a diaphragm modification material in a lithium-sulfur battery. At a current density of 2C, the initial discharge capacity was 897 mAh g -1 After 100 cycles of charge and discharge, the capacity attenuation rate is 0.07%, which has good cycle performance.
[0060] Comparative Example 1
[0061] The preparation method of the NC material of this comparative example comprises the following steps:
[0062] (1) 4 g of melamine was added to 50 ml of deionized water and dispersed uniformly by ultrasonic treatment;
[0063] (2) subjecting the solution in step (1) to hydrothermal treatment at 200° C. for 12 h, filtering the product after the treatment, and then drying to obtain a precursor powder;
[0064] (3) The precursor powder obtained in step (2) was fully mixed with 1 g of hexamethylenetetramine, and then placed in a tube furnace under an argon-hydrogen atmosphere at 10 °C min -1 The temperature was raised to 520℃ at a rate of 2℃min, kept at this temperature for 2h, and then -1The temperature was raised to 800°C at a rate of 1.50 °C, kept at that temperature for 2 h, and then cooled to obtain the comparison material NC;
[0065] The modified material is prepared into a modified membrane, wherein the modified membrane uses polypropylene as the membrane matrix; the coating material is prepared by mixing the modified material, conductive carbon black and polyvinylidene fluoride in an N-methylpyrrolidone solvent in a ratio of 8:1:1, and then coated on the membrane matrix and dried at 30°C for 12 hours to obtain the modified membrane.
[0066] The present invention has no special requirements for the preparation method of the lithium-sulfur battery with the modified diaphragm, and a method well known in the art can be used. For example, the lithium-sulfur battery includes a sulfur positive electrode sheet, a metal lithium negative electrode sheet and an electrolyte, the sulfur positive electrode sheet is made of a carbon / sulfur composite material, and its carbon / sulfur mass ratio is 1:3. The charge and discharge voltage range of the lithium-sulfur battery is 1.7V-2.8V.
[0067] like Figure 4 , which are Tafel curves of a symmetrical cell of MoNQDs / NC prepared in Example 1 and NC prepared in Comparative Example 1. It can be observed from the figure that MoNQDs / NC has a higher exchange current density, indicating that it can accelerate the conversion kinetics of polysulfides and achieve excellent catalytic performance.
[0068] like Figure 5 As shown, this is a rate performance diagram of MoNQDs / NC prepared in Example 1 and NC prepared in Comparative Example 1 as diaphragm modified materials in lithium-sulfur batteries. In different current density tests, MoNQDs / NC exhibited excellent cycle reversibility and rate performance.
[0069] like Figure 6 As shown, the self-discharge performance of MoNQDs / NC prepared in Example 1 and NC prepared in Comparative Example 1 as diaphragm modified materials in lithium-sulfur batteries. After 72 hours of storage, MoNQDs / NC has only 3% capacity loss, and the capacity is restored after cycling, indicating its excellent anti-self-discharge performance.
[0070] like Figure 7 As shown in the figure, the MoNQDs / NC prepared in Example 1 is used as a membrane modification material at a sulfur loading of 9.1 mg cm -2 Cycling performance diagram of lithium-sulfur battery. After 50 cycles, the battery surface capacity is still more than 8 mAh cm -2 , which is twice the surface capacity of commercial lithium-ion batteries, and the capacity decay rate per cycle is as low as 0.1%.
Claims
1. A method for preparing a molybdenum nitride quantum dot / two-dimensional layered carbonitride composite material, characterized in that: The following steps are involved: (1) ultrasonically dispersing a molybdenum source in deionized water to obtain a molybdenum source solution; (2) ultrasonically dispersing the carbon source in the molybdenum source solution, performing solid-liquid separation after hydrothermal treatment, and drying to obtain a precursor powder; (3) The precursor powder is mixed with a nitrogen source and calcined in two stages under an argon-hydrogen atmosphere to obtain a molybdenum nitride quantum dot / two-dimensional layered nitrogen carbonization composite material, denoted as MoNQDs / NC.
2. The preparation method according to claim 1, characterized in that: In step (1), the molybdenum source is selected from one of ammonium molybdate, calcium molybdate and sodium molybdate.
3. The preparation method according to claim 1, characterized in that: In step (2), the carbon source is selected from one of urea, dicyandiamide and melamine, and the mass ratio of the carbon source to the molybdenum source is 1 to 10:
1.
4. The preparation method according to claim 1, characterized in that: In step (2), the temperature of the hydrothermal treatment is 180 to 240° C., and the time is 12 to 24 hours.
5. The preparation method according to claim 1, characterized in that: In step (3), the nitrogen source is selected from one of polyacrylonitrile, ammonium chloride, hexamethylenetetramine and diaminomaleonitrile, and the mass ratio of the nitrogen source to the molybdenum source is 1 to 5:
1.
6. The preparation method according to claim 1, characterized in that: In step (3), in the argon-hydrogen atmosphere, the volume ratio of argon to hydrogen is 9-19:1; the specific process of the second-stage calcination is: firstly heating to 500-550°C, keeping warm for 1-3 hours, then heating to 750-850°C, keeping warm for 1-3 hours.
7. A molybdenum nitride quantum dot / two-dimensional layered carbonitride composite material obtained by the preparation method according to any one of claims 1 to 6.
8. The use of the molybdenum nitride quantum dot / two-dimensional layered carbonitride composite material according to claim 7, characterized in that: It is used as a modified material to prepare a modified diaphragm for lithium-sulfur batteries.
9. A modified diaphragm for lithium-sulfur battery, characterized in that: It comprises a base film and a modified material compounded on the surface of the base film, wherein the modified material comprises the molybdenum nitride quantum dot / two-dimensional layered carbonitride composite material as claimed in claim 7.
10. A lithium-sulfur battery, comprising a positive electrode, a separator and a negative electrode which are compounded in sequence, characterized in that: The diaphragm described therein is the modified diaphragm described in claim 9.
Citation Information
Patent Citations
Carbon nitride nanosheet loaded indium vanadate quantum dot photocatalyst as well as preparation and application thereof
CN112495411A
Preparation method of high-catalytic-activity composite material and application of high-catalytic-activity composite material in lithium-sulfur battery
CN117038901A
Smart acid value measuring apparatus
KR102797372B1
Cited By
Preparation method and application of CoxNiyS / HRGO / PP modified diaphragm of lithium-sulfur battery
CN121261053A
